PENGARUH IMPLEMENTASI SEED BILL ACT 2004 TERHADAP GERAKAN SOSIAL PETANI KAPAS DI INDIA TAHUN 2004 - 2010 - Listya Dewi, Ni Nyoman Clara; Dharmiasih, D.A Wiwik; Resen, Putu Titah Kawitri (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2017)
The increasing demand of the world market for Indian cotton, made the Indian Government issued a policy regulating the production, distribution, and management of cotton seeds called the Seed Bill Act 2004. After the implementation of Seed Bill Act 2004, problems arose directly related to the life of Indian cotton farmers. The Seed Bill Act 2004 is considered do not reflect the interest of Indian cotton farmers. This study analyzes the phenomenon through the response of cotton farmers after the implementation of the Seed Bill Act 2004. This study was analyzed by qualitative descriptive method and also using public policy and Intermestic concept. The data in this study were obtained from various sources such as books, journals, and other sources directly related to this research. The tempus of the study is the years 2004 - 2010. This research found that the obligation of seed certification and the inclusion of GMO seeds in the Seed Bill Act 2004 gave the bad impact on the social and economic life of cotton farmers that resulting respons up to form mass suicide. Keywords: Cotton Seed, Seed Bill Act, Response, Transgenic Seed